Leveraging Community Institutions to Support Agri-Business and Livelihoods in Jharkhand - Bihari, Bipin; Khanuja, Jasmeet; Kothari, Anand; Newton-Lewis, Tom; Singh, Gurpreet (World Bank, Washington, DC, 2020)
The JOHAR project was initiated in 2017 to aid targeted rural producer households to diversify and enhance their household income, and achieve a significant increase in real income until 2023 in selected blocks of rural Jharkhand. The JOHAR project recently completed a baseline for the project evaluation using a randomized controlled trial, supplemented with a non-random control group outside the program area that provides a counterfactual based on an additional quasi-experimental design. The purpose of this note is to present key baseline results and how they validate the project's theory of change. It summarizes the findings from the baseline, presents the status-quo on potential JOHAR beneficiaries, and outlines how the project can achieve its target of enhancing and diversifying the income of rural producer households.